NURSES’ KNOWLEDGE AND ATTITUDES REGARDING PATIENT SAFETY AND FACTORS ASSOCIATED TO IT - AKRAM, S; BIBI, F; PARVEEN, N (Biological and Clinical Sciences Research Journal, 2024)
Patient safety is a critical aspect of healthcare, and nurses' knowledge and attitudes play a vital role in ensuring safety standards are maintained. Understanding the factors influencing nurses' knowledge and attitudes can help develop strategies to improve patient safety. Objective: To assess nurses’ knowledge and attitudes regarding patient safety and identify factors influencing these aspects. Methods: A cross-sectional study was conducted in the Nursing Department of a tertiary care hospital from May 2023 to May 2024. A total of 330 full-time nurses were included in the study. Data were collected using a pre-tested 53-item questionnaire available in both English and Urdu. The questionnaire comprised four sections: demographics (age, sex, qualification, and work experience), knowledge about patient safety, attitudes toward patient safety, and factors associated with knowledge and attitude. Statistical analysis was performed to identify factors significantly associated with good knowledge and attitudes, with a p-value of <0.05 considered significant. Results: Regarding patient safety knowledge, 49% of nurses had good knowledge, with a mean score of 67.2%. The mean attitude score was 62.4%, and 57% (95% CI: 52.6-60) of participants demonstrated good attitudes towards patient safety. Factors significantly associated with good knowledge included age, qualification, work experience, and prior education and training about patient safety (p<0.05). Age and previous education and training about patient safety were significantly associated with good attitude (p≤0.05). Conclusion: The study revealed that while nurses exhibited moderate knowledge, their attitudes toward patient safety were generally favorable. More years of work experience, higher education, and training significantly contributed to better knowledge and attitudes. Implementing targeted educational and training programs can further enhance nurses' knowledge and attitudes toward patient safety.